2010
DOI: 10.15517/rbt.v0i0.3374
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacillus thuringiensis soil isolates from Cuba, with insecticidal activity against mosquitoes

Abstract: Chemical insecticides may be toxic and cause environmental degradation. Consequently, biological control for insects represents an alternative with low ecological impact. In this work, three soil isolates (A21, A51 and C17) from different regions of the Cuban archipelago were identified, characterized and evaluated against Aedes aegypti and Culex quinquefasciatus. The new isolates were compared with reference IPS82 strain and two strains isolated from biolarvicides Bactivec and Bactoculicida, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…There are reports of extensive isolation of the Bacillus genus in Cuba but these focused on the control of agricultural pests (Carreras 2009). In a previous short screening, three Cuban native strains with activity against Diptera of medical importance were isolated (González et al 2011). The present study was oriented to isolate enthomopathogenic bacteria against vectors of human illness also, but a higher number of samples from the western region of the Cuban archipelago were processed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports of extensive isolation of the Bacillus genus in Cuba but these focused on the control of agricultural pests (Carreras 2009). In a previous short screening, three Cuban native strains with activity against Diptera of medical importance were isolated (González et al 2011). The present study was oriented to isolate enthomopathogenic bacteria against vectors of human illness also, but a higher number of samples from the western region of the Cuban archipelago were processed.…”
Section: Discussionmentioning
confidence: 99%
“…quinquefasciatus and Ae. aegypti than did the reference strain 266/2, which has been applied in Cuba for mosquito control (González et al 2011). In all these isolates a similar pattern protein was observed, with the major proteins of 135, 78, 66, and 27 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus thuringiensis soil isolates A21, A51 and C17 isolated from different regions of the Cuban archipelago showed higher larvicide activity than Bactivec's isolated reference strain, against both Aedes aegypti and Culex quinquefasciatus (González et al, 2011). Accordingly, This study describe the isolation and identification of novel isolates of B. thuringiensis, in order to study insecticidal activity of isolates produced proteins against Red Palm Weevil insect.…”
Section: The Red Palm Weevil (Rpw)mentioning
confidence: 97%
“…Studies indicate that such physical characteristics, as observed in the isolates, are associated with gram positive rod-shaped bacteria. [37][38][39][40][41][42][43] …”
Section: Physical and Morphological Characterization Of Isolatesmentioning
confidence: 99%